STRATEGI KOMUNIKASI PEMASARAN RORO CATERING DALAM MENINGKATKAN JUMLAH KONSUMEN DI KOTA PEKANBARU - Didi Alfian; Anuar Rasyid (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The number of larger and more well-known catering businesses and emerging new businesses of the same type have created competition between business partners, even though the Roro Catering business has been around for a long time, it certainly requires business owners to improve the quality of the products they offer and provide the best service to consumers. The purpose of this study was to determine Segmentation, Targeting and Positioning (STP), elements of marketing communication strategy, and Word of Mouth strategy.This study used descriptive qualitative method. The subjects in this study consisted of three research subjects as informants through purposive techniques. The primary data technique in this study was obtained from observations in the Roro Catering office, where the data collected were grouped into three parts, namely: observation, interviews with the owner, employees and some consumers, and documentation. The data analysis technique in this study used the interactive data model of Miles and Hiberman. Checking the validity of the data used the participation extension technique and triangulation.Based on the results of the author's research in the field that, Roro Catering uses a marketing communication strategy seen from segmentation, targeting and positioning. In the segmentation Roro Catering is aimed at the Pekanbaru community, while the targeting is aimed at all groups ranging from ordinary people, officials, government agencies, private companies and other circles. . Meanwhile, the positioning of Roro Catering is to maintain product quality. Furthermore, based on elements of marketing communication in the form of advertising carried out by Roro Catering with the internet, the Web, the social media Facebook and Instagram. in face-to-face sales activities is to offer products to consumers who come to the office, in public relations activities, Roro Catering maintains good relations with government agencies, the police and other agencies, through the form of sales promotion is giving discounts, and finally through marketing activities direct is via telephone and e-mail so that it can make it easier for consumers to order the products offered by Roro Catering. The strategy in the form of a Word of Mouth that is carried out is to give messages to consumers who have used their services to assess other products and services. If you feel satisfied with the services provided, in order to convey it to other potential customers. Keyword: Strategy, Marketing, Communication.